Respostas
respondido por:
12
Xvv =- b/2a
-1=-k /2*1
-k = -2
k = 2
========
Yv = - (b² - 4ac) /4*a
- 4= - (2² - 4*1*m) / 4
-16 = - ( 4 -4m )
-16 = -4 + 4m
-16+4 = 4m
4m = -12
m =-12/4
m= -3
==================
K + m =
2-3= -1 RESPOSTA
-1=-k /2*1
-k = -2
k = 2
========
Yv = - (b² - 4ac) /4*a
- 4= - (2² - 4*1*m) / 4
-16 = - ( 4 -4m )
-16 = -4 + 4m
-16+4 = 4m
4m = -12
m =-12/4
m= -3
==================
K + m =
2-3= -1 RESPOSTA
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás